혈액관류요법에 의하여 성공적으로 치료한 중증 clozapine 중독 1예 - 김화종; Hwa Jong Kim; 김수지; Su Ji Kim; 이관현; Kwan Hyun Lee; 길효욱; Hyo Wook Gil; 양종오; Jong Oh Yang; 이은영; Eun Young Lee; et al. (Kidney research and clinical practice, 2009)
Clozapine, a psychotropic drug commonly used in the treatment of schizophrenia or schizophrenic affective disorders may show side effects such as agranulocytosis, cardiomyositis, cognitive and motor depression in therapeutic doses and central nervous system depression, respiratory depression, arrhythmia, seizures, and even death in case of severe intoxication, warranting an aggressive treatment. We hereby report a case of clozapine overdose patient who ingested a potentially fatal dose of 3 grams and showed stuporous mental state, who was treated successfully by hemoperfusion without any sequelae.